2007
DOI: 10.1098/rsif.2007.1100
|View full text |Cite
|
Sign up to set email alerts
|

When individual behaviour matters: homogeneous and network models in epidemiology

Abstract: Heterogeneity in host contact patterns profoundly shapes population-level disease dynamics. Many epidemiological models make simplifying assumptions about the patterns of disease-causing interactions among hosts. In particular, homogeneous-mixing models assume that all hosts have identical rates of disease-causing contacts. In recent years, several network-based approaches have been developed to explicitly model heterogeneity in host contact patterns. Here, we use a network perspective to quantify the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
680
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 638 publications
(723 citation statements)
references
References 71 publications
8
680
1
4
Order By: Relevance
“…Networks exhibiting heterogeneity in connectivity have a right-skewed degree distribution: a few individuals have many connections, and most individuals have few connections. Such networks with highly connected nodes, or hubs, facilitate rapid disease transfer [31,32], efficient air-traffic flow [33], problemsolving in human groups [1] and the rate of neuron activation, synchronization and response times in neural networks [34]. Other attributes of network structure, beyond the scope of the present work, may also expedite or slow down the rate of information transfer [1,34].…”
Section: Introductionmentioning
confidence: 99%
“…Networks exhibiting heterogeneity in connectivity have a right-skewed degree distribution: a few individuals have many connections, and most individuals have few connections. Such networks with highly connected nodes, or hubs, facilitate rapid disease transfer [31,32], efficient air-traffic flow [33], problemsolving in human groups [1] and the rate of neuron activation, synchronization and response times in neural networks [34]. Other attributes of network structure, beyond the scope of the present work, may also expedite or slow down the rate of information transfer [1,34].…”
Section: Introductionmentioning
confidence: 99%
“…disease outbreaks) are influenced by the connectivity of individuals [15][16][17]. The incorporation of social network theory into models of disease dynamics has shown that the structure of the interaction network and the processes that underlies its formation can affect transmission rate [18][19][20]. Therefore, empirical studies of the processes that drive social network formation are crucial for our understanding of disease dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, populations harbouring a greater diversity of genotypes [8], behavioural phenotypes [9] and patterns of social interactions [10,11] can reduce the spread of infectious agents. However, few studies have compared the relative influence of the individual traits of the index case versus the collective traits of the susceptible population (i.e.…”
Section: Introductionmentioning
confidence: 99%